Transparency in the foreign exchange market and the volume of international trade - Udo Broll; Bernhard Eckwert (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
In this paper we study the impact of more transparency in the foreign exchange market on the ex ante expected volume of international trade. Transparency is measured by the informational content of publicly observed signals correlated to the random exchange rate. We find that more transparency may increase or decrease the volume of international trade. In particular, the impact of more transparency depends the curvature of the marginal cost function of the firms. Furthermore, ex ante expected profits of the firms are higher when the foreign exchange market is more transparent.
Keywords: D8; D51; F21; F31; 330; exchange rate risk; transparency; export production; futures markets